Environmental scanning: how developed is information acquisition in Western European companies? - David Benczur (Information Research: An International Electronic Journal)
A number of theoretical works focus on the potential revolutionary impact of the Internet and other Information and Communication Technologies (ICT) upon Competitive Intelligence, but only a few empirical research papers can be found on it. Is the real impact still unknown, or is it too insignificant to talk about? The present paper searches for the answers to this question both in literature and on the field, focusing on the point where the impact is expected to be the greatest: Information Gathering. Important empirical essays in academic literature are overviewed, including extensive American and also French surveys. These works did not report any major development of Environmental Scanning Systems throughout the years or significant changes due to the Internet. Based on literature the authors establish 7 groups of hypotheses with respect to the influence of external environment, internal structure and development of IT on the Information Gathering activities of firms. These hypotheses are then investigated by quantitative methodologies applied to a large sample: a survey of more than 500 firms over two consecutive years. Internal structure shows only partial influence, but for IT and external environment, the correlation was high. On the other hand, firms are still underdeveloped. The presented results provide better understanding of the level of development of Information Gathering in firms and of the factors influencing it, and suggest new ways for further research in order to understand why firms are still underdeveloped.